Mode of presentation of juvenile diabetes. Issue 6029 (24th July 1976) - Hamilton, D V; Mundia, S S; Lister, J
Abstract : In a study of 66 children with juvenile diabetes symptoms had often present for over a month before diagnosis. Though polyuria, polydipsia, and weight loss were the commonest features, other important symptoms included tiredness lethargy, and malaise. A gradual onset of diabetes was commoner than is generally realised.